MEDIA PEMBELAJARAN BERBASIS CANCA UNTUK MENINGKATKAN HASIL BELAJAR DI SMP NEGERI 1 KISARAN - Riska Wahyuni Lubis; Nila Sudarti; Yuliana (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Bahasa dan Seni, Universitas Negeri Medan, 2024)
This study aims to describe the improvement of student learning outcomes through Canva-based learning media at SMP Negeri 1 Kisaran. The type of research used is Classroom Action Research (CAR) with the Kemmis and Taggart model consisting of four steps, namely: planning, action, observation, and reflection. This research was conducted in Class VIII-7 at SMP Negeri 1 Kisaran in the 2022/2023 Academic Year with 31 students. Based on the results of the study, it shows that Canva-based learning media can improve student learning outcomes. Student learning outcomes in the pre-cycle were 9 students who completed the learning process out of 31 students or 51.62%. In cycle I activities, 25 students who completed the learning process out of 31 students or 80.64%. In cycle II activities, the number of students who completed the learning process increased to 29 students out of 31 students or 93.54%. This shows that student learning outcomes using Canva-based learning media have met effective completion, which is> 85%.